2020
DOI: 10.3389/fonc.2020.01780
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Differentiation Primary Response 88–Cyclin D1 Signaling in Breast Cancer Cells Regulates Toll-Like Receptor 3-Mediated Cell Proliferation

Abstract: Toll-like receptor 3 (TLR3)-mediated apoptotic changes in cancer cells are well-documented, and hence, several synthetic ligands of TLR3 are being used for adjuvant therapy, but there are reports showing a contradictory effect of TLR3 signaling, which include our previous report that had shown cell proliferation following surface localization of TLR 3. However, the underlying mechanism of cell surface localization of TLR3 and subsequent cell proliferation lacks clarity. This study addresses the TLR3 ligand-med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…These results demonstrate that suppression of AQP7 is essential for inhibiting cell cycle arrest in ccRCC. A previous study indicated that PPARα-de cient mice showed accelerated cell regeneration and increased cyclin D1 protein levels [34], and the NF-κB signaling pathway induces and regulates cyclin D1 [35]. Another crucial biological function of PPARα is the suppression of in ammation [36], and in ammation has been identi ed as a pivotal oncogenesis event induced by sustaining HIF activation in ccRCC [37].…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that suppression of AQP7 is essential for inhibiting cell cycle arrest in ccRCC. A previous study indicated that PPARα-de cient mice showed accelerated cell regeneration and increased cyclin D1 protein levels [34], and the NF-κB signaling pathway induces and regulates cyclin D1 [35]. Another crucial biological function of PPARα is the suppression of in ammation [36], and in ammation has been identi ed as a pivotal oncogenesis event induced by sustaining HIF activation in ccRCC [37].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a TLR3 ligand notably increased breast cancer cell proliferation, as indicated by the upregulation of cyclin D1 expression. However, the introduction of a MyD88 inhibitor disrupted the signal transduction of the TLR3-MyD88-NF-kB (p65)-IL6-Cyclin D1 pathway, leading to reduced breast cancer cell proliferation (37). Holleman et al also confirmed that reduced MyD88 expression significantly inhibited MCF-7 cell proliferation (38).…”
Section: Effect Of Myd88 On Breast Cancer Proliferationmentioning
confidence: 99%
“…This culminates in cancer cellular proliferation. Inhibition of MyD88 can suppress the production of IL-6 and cyclinD1 and restrict cancer cell proliferation [50]. Another study suggested that breast cancer cells that transformed to a cancer stem cell phenotype possessed activated TLR3.…”
Section: Tlrs Activation In Immune Response and Inflammationmentioning
confidence: 99%